TEACHER'S USE OF TEXTBOOKS IN TEACHING AND LEARNING PROCESSES - Kurniawati, Nia (2006)
The study sets out to investigate how EFL teachers use the textbook during the classroom instructions in the second and third year classes in SMUN 24 Bandung. To be specific, this study initiates to seek the pictures of the four teachers in using the textbooks and to reveal any factors and reasons underlying their use of the textbooks.Looking at the purpose, it is clearly distinguishable that the study is a descriptive study. This study is guided by four research questions which are going to reveal: 1) teachers' prevalent use of textbooks; 2) teachers' belief underlying the use of the textbooks; 3) teachers' actual use of textbooks in the classroom; and 4) textbooks use aids students' learning.The data for the study were obtained through three instruments-questionnaire, interview, and observation. The subjects of this study were four EFL teachers and their students in SMUN 24 Bandung who taught the second and third year classes. The data obtained from the students were functioned as the additional data providing how the students viewed the way their teachers use the textbooks and teach them.The study found that teachers' beliefs about textbooks determine how often they use the textbooks in the classroom. Teachers' beliefs about teaching also partake in how the teachers make use of the textbooks. For instance, the teachers, who believed that dynamic class is the class where the students were actively involved in the activities, tended to be learner-centered in approaching the teaching activities. They also evaluated their teaching based on students' responses to their teaching performance. They chose the structure of activity that enhanced students' engagement in learning such as discussion and group working.Regarding the actual use of textbooks in the classroom, these four EFL teachers demonstrated three distinct styles of textbook use: a) the 'textbook bound teachers' began the school year with the lesson on page one and progressed page-by-page through the textbook ever the course year (teacher C and D); b) the 'basic' teacher focused on sections that required addition (teacher A); and c) the 'management by objectives' teacher used the textbook in order to ensure that all students acquire minimal competencies (teacher B). The last type of teacher considers that setting the objectives of her teaching and student's learning is important.The students responded negatively to the 'textbook bounded teachers. The students admitted that although the textbook bounded textbooks seem to cover all parts in the textbooks and all skills, they basically developed only one skill of the students. They also stated that the skill they felt progress a lot is the skill the teachers mostly explained and clearly elaborated.This study concludes that teachers' use the textbooks is greatly determined by teachers' beliefs about textbooks and teaching and learning. Regardless they perform the use of textbooks as intended by the curriculum, the way they use or adapt and present the materials in the textbooks to the students contribute to their learning. The result of present study would be valuable data-based for similar studies to view more comprehensive pictures of how EFL teachers in Indonesia use the textbooks in wider scope.